Religious Historiography in a Cross-Cultural Perspective: Review of A History of Christianity in China: 635–1949 - ZHANG, Yongchao (Journal of Research for Christianity in China (JRCC), 2024)
Tao Feiya and Paul Wickeri ed.s, A History of Christianity in China: 635–1949: A Cross-Cultural Perspective, Beijing: Social Sciences Academic Press, 2024 edition.